The impact of Promotional Stimuli and Hedonic Value on Impulse Buying Driven by Positive Emotions Among Tokopedia Users - Intan Dwi Nuraeni; Aala Erpurini (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of e-commerce in Indonesia has influenced consumer purchasing behavior, particularly impulse buying. This study examines the effect of promotion stimuli and hedonic shopping value on impulse buying, with positive emotion as a mediating variable among Tokopedia users in Cimahi City. Using a quantitative approach, adata were collected drom 125 respondents through pusposive sampling and analyzed using SEM-PLS. The result show that promotion stimuli and hedonic shopping value significantly affect positive emotion. However, promotion stimuli and positive emotion do not significantly between variables. In contrast, hedonic shopping value has a significant effect on impulse buying. The findings indicate that impulse buying is primarily driven by hedonic shopping experiences rather promotional strategies or emotional responses, highlighting the importance of enhancing user experience in e-commerce platform.